Corrigendum: Single-cell technologies to decipher the immune microenvironment in myeloid neoplasms: Perspectives and opportunities - Caprioli, Chiara; Nazari, Iman; Milovanovic, Sara; Pelicci, Pier Giuseppe (Frontiers in Oncology, 2022)
In the published article, there was an error in affiliation Number 1. Instead of “Department of Experimental Oncology, Istituto Europeo di Oncologia, Milan, Italy”, it should be “Department of Experimental Oncology, IRCCS Istituto Europeo di Oncologia, Milan, Italy”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.